Postoperative and Recurrent Hematuria after Pretransplant Core Needle Biopsy in Living Donor Kidney Transplant - Yazan Al-Adwan; Navdeep Singh; Pranit N. Chotai; Farjad Siddiqui; Ashley Limkemann; Austin Schenk; Jayanthan Subramanian; W. Kenneth Washburn; Musab Alebrahim; Amer Rajab (Case Reports in Transplantation)
Background. Core needle and wedge biopsies are the two main pathologic ways to determine the suitability of a kidney allograft and to have a baseline allograft biopsy in case of future rejection. Case Presentation. A 57-year-old patient developed a renal arteriovenous fistula causing postoperative and recurrent hematuria after allograft pretransplant renal core needle biopsy and treated with selective Interventional radiology coil embolization. Conclusion. Delayed profound hematuria can be seen after pretransplant core needle renal biopsies and can recur again even after complete resolution, due to arteriovenous fistula formation in the renal calyceal system.